A curious cause of appendicitis. (3rd August 2016) - Stewart-Parker, Emma Patricia; Atta, Mustafa; Doddi, Sudeendra
Abstract : A previously healthy 10-year-old boy presented to the emergency department with central abdominal pain, loose stool and vomiting. He was diagnosed with gastroenteritis, but was well enough to be discharged. The next day he reattended with ongoing diarrhoea and vomiting, with the pain now localised to the right iliac fossa (RIF). Acute appendicitis was suspected, and he was taken for laparoscopic appendicectomy. At surgery, a gangrenous appendix was found, with pus extending from the pelvis up to the liver. The appendix was excised and thorough peritoneal washout performed. Postoperatively, he received 48 hours of intravenous antibiotics and was discharged home. Unfortunately the boy presented again 11 days later with right lower quadrant pain and fever. Ultrasound revealed a collection in the RIF, and he returned to theatre for washout. His recovery was slow until the peritoneal pus sent for bacterial culture grew Salmonella enteritidis, identification of which facilitated appropriate antibiotic treatment.